Soil chemical fumigation alters soil phosphorus cycling: effects and potential mechanisms - Wang, Yan; Tang, Darrell W. S. (Frontiers in Plant Science, 2024)
Soil chemical fumigation is an effective and popular method to increase agricultural productivity.However, the broad-spectrum bioactivity of fumigants causes harm to soil beneficial microorganisms involved in the soil phosphorous cycle, such as soil phosphorus solubilizing microorganisms (PSMs).We review the effects of soil chemical fumigation on soil phosphorus cycling, and the potential underlying mechanisms that ultimately lead to altered phosphorus availability for crops. These complex processes involve the highly diverse PSM community and a plethora of soil phosphorus forms. We discuss phosphatizing amendments aimed at counteracting the possible negative effects of fumigation on phosphorus availability, phosphorus use efficiency, and crop yields. We also emphasize distinguishing between the effects on soil phosphorus cycling caused by the chemical fumigants, and those caused by the fumigation process (e.g. plastic mulching). These are typically conflated in the literature; distinguishing them is critical for identifying appropriate amendments to remediate possible post-fumigation soil phosphorus deficiencies.